A preliminary study on DRGs and spinal cord of a galanin receptor 2-EGFP transgenic mouse. (February 2020) - Lyu, Chuang; Xia, Sheng; Lyu, Gong-Wei; Dun, Xin-Peng; Zheng, Kang; Su, Jie; Barde, Swapnali; Xu, Zhi-Qing David; Hökfelt, Tomas; Shi, Tie-Jun Sten
Abstract: The neuropeptide galanin functions via three G-protein coupled receptors, Gal1 – 3 -R. Both Gal1 -R and 2 -R are involved in pain signaling at the spinal level. Here a Gal2 -R-EGFP transgenic (TG) mouse was generated and studied in pain tests and by characterizing Gal2 -R expression in both sensory ganglia and spinal cord. After peripheral spared nerve injury, mechanical allodynia developed and was ipsilaterally similar between wild type (WT) and TG mice. A Gal2 -R-EGFP-positive signal was primarily observed in small and medium-sized dorsal root ganglion (DRG) neurons and in spinal interneurons and processes. No significant difference in size distribution of DRG neuronal profiles was found between TG and WT mice. Both percentage and fluorescence intensity of Gal2 -R-EGFP-positive neuronal profiles were overall significantly upregulated in ipsilateral DRGs as compared to contralateral DRGs. There was an ipsilateral reduction in substance P-positive and calcitonin gene-related peptide (CGRP)-positive neuronal profiles, and this reduction was more pronounced in TG as compared to WT mice. Moreover, Gal2 -R-EGFP partly co-localized with three pain-related neuropeptides, CGRP, neuropeptide Y and galanin, both in intact and injured DRGs, and with galanin also in local neurons in the superficial dorsal horn. Taken together, the present results provide novel information on the localization and phenotype of DRG and spinal neurons expressing the second galanin receptor, Gal2 -R, and on phenotypic changes following peripheral nerve injury. Gal2-R may also be involved in autoreceptor signaling. Highlights: Gal2 -R-EGFP transgenic mouse is an available model for investigating Gal2 -R protein in nervous system. Gal2 -R-EGFP-LI was mainly seen in the cytoplasm of DRG neurons. The overall protein level of Gal2 -R-EGFP is upregulated in mouse lumbar DRGs after sciatic nerve spared injury. Gal2 -R-EGFP is upregulated in medium-sized NPs, but downregulated in small NPs of DRGs after nerve injury. Gal2 -R-EGFP co-exists with CGRP, galanin and NPY in injured DRGs to some extent.